1996
DOI: 10.1210/jcem.81.1.8550749
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adrenomedullin concentration in patients with heart failure.

Abstract: We measured plasma concentrations of adrenomedullin (AM), a novel bioactive peptide with potent vasodilator activity, in 21 patients with chronic congestive heart failure due to various heart diseases and compared them to levels in age- and sex-matched healthy subjects to examine the pathophysiological role of plasma AM in heart failure. In addition, the relationship between plasma AM and other hormones known to control the cardiovascular system was examined in these patients. The plasma AM level in the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 18 publications
0
75
1
2
Order By: Relevance
“…At the end of the treatment period, no difference was found with respect to the dose of olmesartan used between the two groups: CCB: 22.1 ± 7.7 mg per day; and diuretic: 21.2 ± 8.6 mg per day. The mean doses (mg per day) of CCB and diuretics used were as follows (n): azelnidipine: 13.3 ± 3.9 (15); amlodipine: 3.5 ± 1.3 (13); benidipine: 4 (1); trichlormethiazide: 1.47 ± 0.51 (17); and indapamide: 0.96±0.40 (12). Figure 1 shows the time course of blood pressure and pulse, and the reductions in blood pressure at 1, 3 and 6 months during the treatment period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the treatment period, no difference was found with respect to the dose of olmesartan used between the two groups: CCB: 22.1 ± 7.7 mg per day; and diuretic: 21.2 ± 8.6 mg per day. The mean doses (mg per day) of CCB and diuretics used were as follows (n): azelnidipine: 13.3 ± 3.9 (15); amlodipine: 3.5 ± 1.3 (13); benidipine: 4 (1); trichlormethiazide: 1.47 ± 0.51 (17); and indapamide: 0.96±0.40 (12). Figure 1 shows the time course of blood pressure and pulse, and the reductions in blood pressure at 1, 3 and 6 months during the treatment period.…”
Section: Resultsmentioning
confidence: 99%
“…11 Plasma renin activity and the aldosterone concentration were measured by radioimmunoassays as previously described, and plasma brain natriuretic peptide was assessed using an immunoradiometric assay. 12,13 …”
Section: Measurementsmentioning
confidence: 99%
“…Immunoreactive AM has been shown to be present in human plasma and tissues such as adrenal medulla, lung, kidney, cardiac atrium and ventricle (Ichiki et al 1994, Kitamura et al 1994a, and the plasma AM was reported to be increased in patients with hypertension or heart failure (Ishimitsu et al 1994, Kitamura et al 1994a, Jougasaki et al 1995, Nishikimi et al 1995, Kato et al 1996. We recently found, by chromatographic analyses, that the immunoreactive AM in human plasma consists of two molecular forms of AM: mAM, AM(1-52)-NH 2 , and iAM, a glycine-extended intermediate form of AM that is converted to mAM by an amidation enzyme (Kitamura et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that immunoreactive AM in the human plasma consists, not only of mAM, but also of iAM, which is converted to mAM in the presence of the amidation enzyme in vitro (Kitamura et al 1998). A number of reports have shown that the plasma concentrations of AM are increased in patients with congestive heart failure (CHF) ( Jougasaki et al 1995, Nishikimi et al 1995, Kato et al 1996; however, the molecular forms of plasma AM have not been examined. In those previous studies, the plasma AM concentration was determined by RIAs unable to distinguish mAM from iAM, and was thereby measured as total AM (tAM) concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenomedullin has been found in various tissues, including vascular smooth muscles, kidneys, cardiac tissues and lungs [2,3]. Previous studies reported that the plasma concentration of adrenomedullin increases in patients with hypertension, renal failure and congestive heart failure [4,5], though the major source of circulating adrenomedullin is unknown. Adrenomedullin has vasodilator and antiproliferative actions in vascular smooth muscle and glomerular mesangium [6,7], as a paracrine or autocrine mechanism [8].…”
mentioning
confidence: 99%